Virtual Reality, a Method to Achieve Social Acceptance of the Communities Close to Mining Projects: A Scoping Review - López-Casaperalta, Patricia (2022)
“Background: Virtual reality (VR) technology is an effective, interactive and immersive type of communication since it produces greater interest and attention in the user, thereby allowing greater understanding and comprehension than with more traditional methods. On the other hand, not much information is known about the application of this novel technology in the context of social acceptance as far as the mining sector is concerned; our approach and methodology were based on scoping review (Prisma-SrC, Daudt et al., Arksey, and O’Malley). The research terms were also planned before, with the aim of carrying out three posterior screening levels, among which was the use of EndNote 20 and the PICO framework. Exhaustive research was carried out in nine databases. We obtained n=2 research articles of n=923 initially found, all of which went through three levels of filtering. The chosen articles were evaluated according to Hawker et al. 's methodological rigor, to be included in the review. This scoping review could be the starting point for a series of further investigations that would fill the gap in the literature on this topic, emphasizing experimental articles to confirm the impact of virtual reality technologies on the communities within the sphere of influence of a mining project.“